Studi komparasi fungsi traffic island Taman Rama Shinta dengan traffic island Taman Patung Tualen di Badung, Bali - Ida Bagus Kade Adi Putra; I Gusti Agung Ayu Rai Asmiwyati (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2026)
Traffic islands serve to regulate traffic flow and provide temporary waiting spaces for pedestrians. However, there are indications of a functional shift at the Taman Rama Shinta Traffic Island (TITRS) in Mengwi due to physical elements that do not align with its designated function, such as seating facilities and a garden design with access from multiple directions. Meanwhile, the Taman Patung Tualen Traffic Island (TITPT) in South Kuta demonstrates a function that aligns more closely with existing regulations. These differences indicate a hypothesis that physical elements may influence the functional shift of a traffic island. This study aims to inventory existing conditions, compare the functions of TITRS and TITPT, and provide design recommendations based on regulations and user perceptions. The research method uses a survey method approach through field observation, questionnaires, and interviews. The comparison is based on three variables: function, facilities, and site character elements, with reference to the Minister of Transportation Regulation No. PM 48 of 2023. The results show that TITRS has undergone a functional shift, while TITPT continues to function as a passive traffic island. Design recommendations include limiting access and removing seating at TITRS, and improving the landscape quality of TITPT. This research is expected to serve as a reference for managers in organizing traffic islands in accordance with their intended function.